The Limitations of Vocational Training Policies for Ethnic Minority Youth – A Case Study in Hoa Binh Province - Minh, Bui Thanh (VNU Journal of Science: Policy and Management Studies, 2019)
Vocational training for ethnic minority youth has been identified as an important solution to create sustainable livelihoods for people, narrowing the development gap among ethnic groups so as to ensure social security for the whole population. The Vietnamese state has enacted many policies to help young ethnic minority people participate in vocational training but the results are not as effective as expected. These restrictions come from not only the inside content of the policies themselves but also from the conditions in which they are implemented. The paper employs the ROCCIPI analytical framework and the quick survey results on vocational training for ethnic minority youth in Hoa Binh to provide an overview of these limitations and their impacts in reality.